PERBANDINGAN MELALUI PENDEKATAN HUKUM TERHADAP HAK PENYANDANG DISABILITAS DALAM PENYEDIAAN FASILITAS: INDONESIA, AMERIKA SERIKAT, DAN MESIR - Kurnia, Eyda (LPPM Universitas Bina Bangsa, 2024)
Accessibility of public facilities for people with disabilities is a crucial issue in various countries. This research aims to compare the legal approaches adopted by Indonesia, the United States, and Egypt in ensuring the provision of accessible facilities for people with disabilities. The three countries have implemented different legal approaches. Indonesia relies on specific written regulations, the United States uses comprehensive legislation, and Egypt combines elements of both approaches. This research uses a qualitative approach with a normative juridical research type. Primary data was obtained from primary legal materials such as laws and regulations in the three countries. Secondary data includes books, scientific journals, articles, and other relevant scientific works. The research results show that the three countries have demonstrated commitment to ensuring the accessibility of facilities for people with disabilities. However, there are still various challenges in implementation, such as compliance gaps, weak enforcement mechanisms, and a lack of public awareness